Tetra-linoleoyl cardiolipin depletion plays a major role in the pathogenesis of sarcopenia. (June 2019) - Semba, Richard D.; Moaddel, Ruin; Zhang, Pingbo; Ramsden, Christopher E.; Ferrucci, Luigi
Abstract: Sarcopenia, the progressive loss of muscle mass, strength, and physical performance that occurs during aging, is highly prevalent among the elderly. Sarcopenia increases the risk of falls, disability, and death. The biological basis for sarcopenia is not well understood. There are no specific preventive or therapeutic strategies for sarcopenia except exercise. The elucidation of biological pathways and identification of therapeutic targets for treating or preventing sarcopenia remain a high priority in aging research. Mitochondria play a critical role in skeletal muscle by providing energy in the form of ATP, regulation of signaling, calcium homeostasis, autophagy, and other functions. Cardiolipin, a unique dimeric phospholipid specific to mitochondria and an essential component of mitochondrial membranes, is involved in mitochondrial protein transport, maintaining structural organization of mitochondrial membranes, cellular signaling, regulating enzymes involved in β-oxidation of fatty acids, and facilitating normal electron transport chain (ETC) function and generation of ATP. The fatty acid species composition of cardiolipin is critical to mitochondrial bioenergetics, as cardiolipin affects membrane biophysical properties, binds and stabilizes ETC protein complexes, and shapes the curvature of the mitochondrial cristae. Tetra-linoleoyl cardiolipin (18:2)4 comprises ∼80% of cardiolipin in mitochondria in normal human skeletal and cardiac muscle and is optimal for effective ETC function and ATP generation. Aging is associated with a decrease in cardiolipin content, decrease in tetra-linoleoyl cardiolipin (18:2)4 and replacement of linoleic acid (18:2) with other fatty acids in cardiolipin composition, decline of ETC function, and increased generation of reactive oxygen species in muscle. Together, these findings from the literature prompt the hypothesis that depletion of the cardiolipin (18:2)4 species may be at the root of mitochondrial dysfunction with aging, in turn leading to sarcopenia. Corroboration of the tetra-linoleoyl cardiolipin depletion hypothesis suggests new leads for the prevention and treatment of sarcopenia by enhancing the biosynthesis, accretion, and integrity of tetra-linoleoyl cardiolipin.